Review of Food Estate Legal Policy in Maintaining Food Sovereignty Based on State Obligations - Laga Sugiarto; Ishaq Dhimas Bayuaji (Law Research Review Quarterly, 2026)
This study analyzes the legal framework of Indonesia's Food Estate policy, evaluating its alignment with the constitutional mandate of Food Sovereignty and State Obligations. Employing normative legal research with Regulatory Impact Assessment (RIA) and ROCCIPI frameworks, the study diagnoses regulatory disharmony and effectiveness. The findings reveal a fundamental paradigm shift from "Food Sovereignty" to "Food Security" within the Food Estate regulations, characterized by a corporate-centric approach that marginalizes local farmers. The research identifies critical vertical and horizontal disharmonies, particularly between the Forestry Law and implementing regulations, which facilitate land conversion in protected forests and weaken environmental safeguards through "Fast KLHS" mechanisms. This creates a "state of exception" that risks repeating historical ecological failures. The study concludes that the current policy contains structural legal flaws violating the state's obligation to respect and protect human rights. It recommends an immediate moratorium on land clearing in protected areas, regulatory harmonization, and a strategic pivot towards a community-based food sovereignty model.